Adsorption of n-butylparaben from aqueous solution on surface of modified granular activated carbons prepared from African palm shell. Thermodynamic study of interactions. Issue 4 (August 2020) - Moreno-Marenco, Astrid Roxanna; Giraldo, Liliana; Moreno-Piraján, Juan Carlos
Abstract: Butylparaben (BuPB) is used as preservative in foods, pharmaceuticals and personal care products, so it is possible to find it in surface waters, which causes problems for the environment to their classification as emerging contaminant, due to its ability to act as endocrine disruptor. Activated carbons from African palm shell ( Elaeis guineensis ) by chemical modification with CaCl2 and MgCl2 solutions at different concentrations were prepared, in order to assess their influence on the textural and chemical properties for butylparaben (BuPB) adsorption from aqueous solution. The activated carbons have a surface area and pore volume ranging between 608-1320 m 2 . g -1 and 0.25-0.52 cm 3 . g -1, respectively. BuPB adsorption capacity varies between 0.74-1.38 mmol.g −1 . Based on the obtained results, the effect of the concentration of the activating agent on the carbon activation process is evidenced, favoring the physicochemical characteristics of the coals at a low salt concentration, presenting a decrease with the increase in the concentration. While the nature of salt has little effect on the developed characteristics. The thermodynamic study was performed, finding negative immersion enthalpy ( Δ H i m m < - 16.87 J . g - 1 ) obtained from immersion calorimetry, indicating the exothermic nature of the adsorption process that involves adsorbate-adsorbent and solvent-adsorbent interactions, while the adsorbate-adsorbent interaction ( Δ H i n t < 37.64 J . g - 1 ) is an endothermic process, which has an energy requirement to be carried out.